Como se faz um tijucano? Reflexões sobre consumo, identidade e masculinidade em um bairro carioca - Cupolillo, Flávia Braga Nogueira (2007)
The love of cariocas for the city of Rio de Janeiro is widely known. As well as the cariocas, there is another social group, called tijucanos, which the love for the neighborhood is peculiar. The Tijuca zone, known by its tradition and development during the 60¿s, due to his local identity ¿ tijucana, definitely deserves prominence in the ¿wonderful city¿. The people of Tijuca can be known as a ¿personality¿ in Rio, and their habits of consumption seldom exceed the area¿s limits. Enclosure of histories and special characteristics, how to be a tijucano, an adjective that people of Tijuca are proud of, is one of the focus of this present study. To be an unconditional tijucano, who loves to walk around in the neighborhood, in the square, enjoy their lives in famous bars, ended up as a peculiarity in the carioca scenario, together with the people of Ipanema, Barra and many others, that together make Rio de Janeiro a unique city. In spite of the increasing visibility, there are few studies trying to understand the way heterosexual men interact with the world of consumer goods. In view of the great interest and in the contemporary world, the meaning of consumption has increased. The object of the present study is to try to understand how the people from Tijuca use the world of consumer goods to ¿become a man¿, i.e., to construct their male heterosexual identity. This analysis is crucial to investigate the construction of masculine gender identity of the people from Tijuca. The study was based on data gathered through deep interviews with nine men from Tijuca during the month of January 2007. The results have shown that the tijucanos interact with the neighborhood services and locals during the process of construction of gender and local identity. It was possible to notice that there are four differents stages, by means of, people use the world of consumer goods to identify themselves as men from Tijuca. Therefore, it is possible to conclude that it occurs the consumption of specific products and places in strategy to: define masculinity and local identity (when young person), move aside, assimilation, acceptation and reinforcement of that identity.